Frequency of Diabetes Mellitus in Females with Breast Cancer - Imran, Ragda; Ali, Haider; Arslan , Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the frequency of diabetes in patients with breast cancer. Study Design: Cross sectional study. Place of study and duration: Department of Medicine, Shaukat Khanum Memorial Cancer Hospital & Research Center Lahore for 6 months from 1st July 2024 to 31st December 2024. Patients & Methodology: One hundred and forty patients with breast cancer were enrolled through non-probability consecutive sampling technique. About 3ml blood sample was taken for assessment of HbA1c. Reports were assessed and if HBA1c>6.5%, then diabetes was labeled. Results: In this study the mean age of the participants was 50.84 ± 8.61 years, with a mean BMI of 24.48 ± 3.94 kg/m² and 42 (30%) had hypertension. A family history of breast cancer was reported in 25 (17.9%) participants. among 140 breasts cancer females 27 (19.29%) were diabetics. Diabetes was present in 4 (5.9%) patients aged ≤50 years, while in 23 (31.9%) older than 50 years (p-value <0.001). Diabetes was more common among overweight and obese patients 17 (26.6%) as compared to patients with normal BMI [10 (13.2%)] (p-value = 0.045). Diabetes was more common in patients with advanced stage cancer [11 (25.0%) in Stage II and 15 (26.8%) in stage III] than stage I [1 (2.5%), p-value = 0.006). Diabetes was significantly more prevalent in hypertensive patients [24 (57.1%)] than non-hypertensive [3 (3.1%), p-value <0.001). Patients receiving chemo- as well as radiotherapy are at more risk of diabetes (100%) as compared to patients receiving only chemotherapy (6%) or radiotherapy (18.5%). Conclusion: On the findings of this study, we may conclude that frequency of diabetes mellitus is 19.29% in females presenting with breast cancer.